Repetition, Reputation, and Raiding - Leach, J. Chris (Review of Financial Studies, 1992)
I develop a multitarget takeover model with bid revisions, in which bidders desire a reputation for having low valuations. Such a reputation increases the likelihood that future targets will accept low premium bids. Bidders develop reputation by using low take-it-or-leave-it offers. Consequently, tender premiums bid revision rates, and success rates are lower for continuing bidders than for those considering only a single target. Success rates vary within a series, and reputation building is more likely with highly correlated target valuations. I provide an exploratory empirical analysis consistent with lower premiums from continuing bidders and discuss some resulting implications regarding "raiders, " conglomerates, and resistance strategies. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.